Let's go through Angie's solution step by step.
The original equation is: \[ -x + 7 = -11 \]
-
Subtract 7 from both sides: \[ -x + 7 - 7 = -11 - 7 \] This simplifies to: \[ -x = -18 \]
-
To solve for \(x\), multiply both sides by -1 (or divide by -1): \[ x = 18 \]
Angie's final answer states \( x = -18 \), which is incorrect.
Her error occurs specifically in the subtraction step where she incorrectly calculates: \[ -11 - 7 = -18 \] This should actually be: \[ -11 - 7 = -18 \] indicating that she set the left-hand side of the equation \( -x = -18 \) correctly, which actually leads to \( x = 18 \).
So the correct response to identify the error is: She did not divide both sides by −1.
Thus, the error in her calculation comes from not correctly converting \( -x = -18 \) to \( x = 18 \).